Production and properties of a medium density wood-cement boards produced with oriented strands and silica fume - Soares Del Menezzi, Cláudio Henrique; Gomes de Castro, Vinicius; Rabelo de Souza, Mário (Maderas. Ciencia y Tecnología, 2014)
Wood-cement board (WCB) is a panel product that has the advantages of inorganic and organic materials. However, the main problems affecting the manufacture and use of WCB are the inhibitory effects of wood on the setting of cement and the high specific gravity of the final product. This paper examines the potential of strand orientation and the use of silica fume (SiO2) to facilitate the production of a medium density WCB from Pinus taeda. Oriented wood-cement boards (OWCB) were manufactured with wood/cement (w/w) ratio of 1:1, specific gravity 850 kg/m3; and SiO2 content as cement replacement of 0%, 10% and 20%. The OWCB were tested for static bending (MOR and MOE) properties in parallel (//) and perpendicular ( ) directions; internal bond (IB); compression strength parallel to surface (CP); thickness swelling (TS) and water absorption (WA). The results showed that replacement of cement with 10% of SiO2, increased MOE (//), MOR (//) and CP and, decreased WA and TS, and most importantly eliminated the inhibitory effect of wood on cement setting. The principle of strand orientation was effective to produce boards with anisotropy in the flexural properties ranging form 2.1 to 2.8 for MOR and 2.6 to 3.8 for MOE. However, boards had very low IB strength and this shortcoming must be addressed in future research.